Meteorites : the story of our solar system - Smith, Caroline 1976-; Russell, Sara S. (Sara Samantha) 1966-; Almeida, Natasha (Buffalo, New York ; Richmond Hill, Ontario : Firefly Books Ltd, 2019)
"A fascinating and authoritative introduction to the science of meteorites, written by leading experts in the field. Meteorites are rocks from space that have fallen to the Earth's surface. Once considered bad omens, they are now recognized for giving us a unique insight into the nature of the material that was present when our solar system formed. In Meteorites, experts from the Natural History Museum in London, England, provide a compelling and up-to-date introduction to these otherworldly objects. This fully illustrated guide reveals: What meteorites are Where meteorites come from What they tell us about our solar system The latest information on key meteorite falls. In clear, jargon-free language, the authors explain how meteorites provide us with invaluable information about planets beyond Earth--both within our solar system and around other stars. With its combination of color photographs, diagrams and maps, Meteorites is the ultimate reference to these mysterious objects from space."--
What are meteorites? -- Where are meteorites found? -- Impacts and collisions -- Sources and types of meteorites -- Comets -- The future.
"A Firefly book"--Title page verso.
"First published by the Natural History Museum, Cromwell Road, London"--Title page verso.
Includes bibliographical references (pages 123-124) and index.
107841
Keywords: Meteorites